KINERJA KEUANGAN DAERAH PADA ERA OTONOMI DAERAH (Suatu Kajian Empiris di propinsi Jawa Timur) - TriPitono Adi Prabowo (Trunojoyo University of Madura, 2006)
The objectives of this study were to empirically compare and analyze the financial performance of municipal/city goverment before and after the autonomy policy. using three measurements for financial performance-expenditure capability, mobility and fiscal decentralization -this study perform the comparison due to